2012
DOI: 10.1128/aem.01646-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Population Structure of Vibrio vulnificus on Fishes from the Northern Gulf of Mexico

Abstract: The prevalence of Vibrio vulnificus on the external surfaces of fish from the northern Gulf of Mexico was determined in this study. A collection of 242 fish comprising 28 species was analyzed during the course of 12 sampling trips over a 16-month period. The prevalence of V. vulnificus was 37% but increased up to 69% in summer. A positive correlation was found between the percentages of V. vulnificus-positive fish and water temperatures, while salinity and V. vulnificus-positive fish prevalence were inversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…When winter is over, vibrios released from the sediment attach to zooplankton and reproduce rapidly as the temperature increases (28). Other factors, such as V. vulnificus-positive fish, were found to be inversely correlated to salinity (Pearson's correlation coefficient r ϭ Ϫ0.91077, P Ͻ 0.0001) and positively correlated to temperature (Pearson's correlation coefficient r ϭ 0.62481, P Ͻ 0.0298) in the northern Gulf of Mexico (24). V. parahaemolyticus was frequently reported from tropical and subtropical oysters (99% positive in Brazil, 94% in India, 100% in the United States, and 71% in Taiwan) (10).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…When winter is over, vibrios released from the sediment attach to zooplankton and reproduce rapidly as the temperature increases (28). Other factors, such as V. vulnificus-positive fish, were found to be inversely correlated to salinity (Pearson's correlation coefficient r ϭ Ϫ0.91077, P Ͻ 0.0001) and positively correlated to temperature (Pearson's correlation coefficient r ϭ 0.62481, P Ͻ 0.0298) in the northern Gulf of Mexico (24). V. parahaemolyticus was frequently reported from tropical and subtropical oysters (99% positive in Brazil, 94% in India, 100% in the United States, and 71% in Taiwan) (10).…”
Section: Discussionmentioning
confidence: 81%
“…The pathogenicity of V. cholerae depends on a combination of properties, including the presence of cholera toxin (CT), encoded by ctxA, and the colonization and adhesion factor encoded by tcpA (22,23). Studies have shown seasonal patterns for this species, with increased occurrence and incidence of wound infections at warmer temperatures (24).…”
mentioning
confidence: 99%
“…vulnificus and V. vulnificus infections have been reported throughout Europe, Scandinavia, South America, the Far East, South Pacific, as well as on all coasts of the United States (15). Along with oysters and other molluscan bivalves and estuarine/coastal waters, V. vulnificus has been reported in fish (82,83,84), sediments (85,86), and plankton (73). The presence of this pathogen appears to be spreading to areas where it was not previously reported, and this is likely due to global warming (see below).…”
Section: Geographic Distributionmentioning
confidence: 83%
“…vulnificus biotype 2 was considered an obligate eel pathogen whose main reservoir was the farmed eel (28). This idea was apparently confirmed by its successful isolation from diseased eels, but not from asymptomatic carriers, tank water (even during the outbreaks), wild eels or other environmental sources (waters, oysters) (1,2,48,49,50,51,52). To demonstrate that water could be a natural reservoir for this biotype, survival experiments in artificial and natural water microcosms over short and long terms (months or years) were performed (53,54).…”
Section: Reservoirs For Biotypementioning
confidence: 99%